2010
DOI: 10.4208/cicp.010909.220110a
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Solution of the Gyroaverage Operator for the Finite Gyroradius Guiding-Center Model

Abstract: In this work, we are concerned with numerical approximation of the gyroaverage operators arising in plasma physics to take into account the effects of the finite Larmor radius corrections. Several methods are proposed in the space configuration and compared to the reference spectral method. We then investigate the influence of the different approximations considering the coupling with some guiding-center models available in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…This is performed on a finite element formalism and enables therefore high order accuracy by keeping the matricial formulation. In [30] the influence of the interpolation operator (which is of great importance when the quadrature points do not coincide with the grid points) has been studied and it is shown that the cubic splines are appropriate. The direct integration on gyro-circles proposed in [30] has been recently generalized to arbitrary coordinates [113] and implemented in the code.…”
Section: Integration On Gyro-circles Using Hermite Interpolationmentioning
confidence: 99%
“…This is performed on a finite element formalism and enables therefore high order accuracy by keeping the matricial formulation. In [30] the influence of the interpolation operator (which is of great importance when the quadrature points do not coincide with the grid points) has been studied and it is shown that the cubic splines are appropriate. The direct integration on gyro-circles proposed in [30] has been recently generalized to arbitrary coordinates [113] and implemented in the code.…”
Section: Integration On Gyro-circles Using Hermite Interpolationmentioning
confidence: 99%
“…The Padé approximation approach has the advantage of being fast, but is well known to cause an overdamping of small scales, which limits its accuracy (Steiner et al 2015). A more common approach is to evaluate directly the gyroaverage integral through numerical quadrature, relying on interpolation on points along the gyroring of the function which is gyroaveraged (Jolliet et al 2007;Crouseilles et al 2010;Görler et al 2011;Steiner et al 2015). By choosing high-order interpolation schemes, high-order accuracy can be achieved with this method, but with a larger computational cost than with a Padé based approach (Steiner et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This is performed on a finite element formalism and enables therefore high order accuracy by keeping the matricial formulation. In [5] the influence of the interpolation operator (which is of great importance when the quadrature points do not coincide with the grid points) has been studied and has shown that the cubic splines are a good candidate. Some techniques used in [5] taking advantages of the cartesian coordinates properties are no more valid in (r, θ) polar geometry.…”
Section: Gyroaverage Operator Definitionmentioning
confidence: 99%
“…In [5] the influence of the interpolation operator (which is of great importance when the quadrature points do not coincide with the grid points) has been studied and has shown that the cubic splines are a good candidate. Some techniques used in [5] taking advantages of the cartesian coordinates properties are no more valid in (r, θ) polar geometry. In this paper we present a method based on a direct integration of the gyroaverage operator which is directly applicable for global gyrokinetic code in toroidal geometry as GYSELA code.…”
Section: Gyroaverage Operator Definitionmentioning
confidence: 99%
See 1 more Smart Citation